2020
DOI: 10.1007/s00018-020-03515-w
|View full text |Cite
|
Sign up to set email alerts
|

A holistic view on plant effector-triggered immunity presented as an iceberg model

Abstract: The immune system of plants is highly complex. It involves pattern-triggered immunity (PTI), which is signaled and manifested through branched multi-step pathways. To counteract this, pathogen effectors target and inhibit individual PTI steps. This in turn can cause specific plant cytosolic nucleotide-binding leucine-rich repeat (NLR) receptors to activate effectortriggered immunity (ETI). Plants and pathogens have many genes encoding NLRs and effectors, respectively. Yet, only a few segregate genetically as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 133 publications
(188 reference statements)
0
47
0
Order By: Relevance
“…This most likely leads to the activation of RNLs and can explain their requirement for basal resistance (see Fig 3 ). (5) It is possible that the aforementioned “weak” recognition and sensor NLR activation is also targeted by other effectors, causing the second ETS [ 62 ]. (6) RNLs are fully required for TNL-mediated immunity (black arrows) with some structural preferences for either ADR1s or NRG1s.…”
Section: Discussionmentioning
confidence: 99%
“…This most likely leads to the activation of RNLs and can explain their requirement for basal resistance (see Fig 3 ). (5) It is possible that the aforementioned “weak” recognition and sensor NLR activation is also targeted by other effectors, causing the second ETS [ 62 ]. (6) RNLs are fully required for TNL-mediated immunity (black arrows) with some structural preferences for either ADR1s or NRG1s.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved prolonged expression of Jsi1 leads to a cell-death phenotype across the different plant species we tested, which may be connected to activation of SA signaling. Studying an effector function in planta, separated from the context of the rest of the effectome, may reveal complex responses derived from initial effector action and subsequent recognition responses by the plant immune system which would usually be counteracted by other effectors in the natural context (Thordal-Christensen, 2020). It was reported that interaction between Six8, a F. oxysporum effector, and TPL leads to activation of SA-defense signaling in A. thaliana (Gawehns et al, 2014).…”
Section: Accepted Articlementioning
confidence: 99%
“…Plants lack a vertebrate-like circulatory system and antibodies to defend themselves from pathogenic attacks; instead, various forms of defense mechanisms have evolved in plants, including pathogen-associated molecular pattern (PAMP)-induced immunity (PTI, previously known as basal resistance), effector-induced immunity (ETI, previously known to as R gene-mediated resistance), and systemic acquired resistance (SAR) [ 3 , 4 ]. PTI and ETI involve dramatic transcriptional reprogramming in the plant, including upregulation of defense genes encoding antimicrobial proteins and enzymes for biosynthesis of anti-microbial secondary metabolites, as well as genes encoding proteins associated with signaling hormones [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%